2000
DOI: 10.1023/a:1012994712851
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Leptin is an adipocyte-derived cytokine with many functions including signaling the status of body energy stores through activation of the leptin receptor (OBR). Activation of the long form of OB-R (OB-Rb) results in JAK2 phosphorylation, activation of STATs, and subsequent gene expression. Activated STAT3 induces SOCS-3 expression in some cell types, which in turn down-regulates the JAK/STAT pathway. Although both leptin and OB-R are expressed in pituitary cells, the mechanism of signal transduction and its r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…2). Previous studies have indicated that STAT3 activation through tyrosine phosphorylation plays an important role in leptin signal transduction at the pituitary gland (Tsumanuma et al 2000, Lloyd et al 2001. Although pituitary cells other than thyrotropes also express leptin receptors (Sone et al 2001), our findings suggest that reduced leptin signalling in the whole pituitary gland might contribute to the abolishment of the direct effect of leptin on TSH secretion from the isolated pituitaries of the hypothyroid rats that were previously studied (Da Veiga et al 2004).…”
Section: Discussionmentioning
confidence: 51%
“…2). Previous studies have indicated that STAT3 activation through tyrosine phosphorylation plays an important role in leptin signal transduction at the pituitary gland (Tsumanuma et al 2000, Lloyd et al 2001. Although pituitary cells other than thyrotropes also express leptin receptors (Sone et al 2001), our findings suggest that reduced leptin signalling in the whole pituitary gland might contribute to the abolishment of the direct effect of leptin on TSH secretion from the isolated pituitaries of the hypothyroid rats that were previously studied (Da Veiga et al 2004).…”
Section: Discussionmentioning
confidence: 51%
“…The long form Ob-Rb is the active form of the receptor [56], and its mRNA is expressed in the pig pituitary [57]. Activation of the Ob-Rb results in Jak2 phosphorylation, activation of STATs and subsequent gene expression [58, 59, 60]. The short form of Ob-R (Ob-Ra) that has been generally thought to be inactive at signaling can actually induce the expression of immediate early genes [61]and transmits signals through MAP kinase [62].…”
Section: Discussionmentioning
confidence: 99%
“…These signals are well described in the hypothalamus and include the JAK2-STAT-3 and the PI 3 kinase pathways [69, 143]. There is also good evidence that PI 3 kinase is expressed in high abundance in the anterior pituitary [144] as is the STAT-3/SOCS-3 signaling system [145,146,147]. Leptin receptors are present in all anterior pituitary cell types [140] and we reported a homogeneous distribution of leptin receptor-ir throughout the prepubertal rat pituitary [134].…”
Section: Pituitary Adipokinesmentioning
confidence: 99%
“…There is evidence that leptin can activate the pituitary JAK-STAT pathway. Using the immortalized HP75 human pituitary cell line, Tsumanuma et al [145] reported that leptin stimulated the expression of socs-3 mRNA and phosphorylation of SOCS-3. Studies in isolated porcine somatotropes revealed that leptin increased intracellular calcium ion levels via JAK-STAT and MAPK pathways [148].…”
Section: Pituitary Adipokinesmentioning
confidence: 99%
See 1 more Smart Citation